U.S.-Mexico free trade agreement : US perspectives. - Wu, Terry (1991)
Examines a variety of issues surrounding the proposed free trade agreement. Reviews the current state of economic relations between the US and Mexico, discussing the implications of a free trade agreement for a number of key US industries. Evaluates the agreement in the context of overall US trade policies and objectives.